2007
DOI: 10.1016/j.juro.2007.05.138
|View full text |Cite
|
Sign up to set email alerts
|

The Change in the Dihydrotestosterone Level in the Prostate Before and After Androgen Deprivation Therapy in Connection With Prostate Cancer Aggressiveness Using the Gleason Score

Abstract: Low dihydrotestosterone in the prostate is probably sufficient to propagate the growth of aggressive prostate cancer. Furthermore, the prostate with aggressive prostate cancer can produce androgens from adrenal precursors more autonomously than the prostate with nonaggressive prostate cancer under a low testosterone environment with testicular suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…We could confirm these findings in our experimental models and found higher SRD5A1 levels in metastasized and hormone-refractory tumors. The association between SRD5A1 expression and Gleason score is in line with the observation that patients with a Gleason score of 7 to 10 PC had a smaller decline of intraprostatic DHT concentrations during hormonal therapy compared with patients with a Gleason score of 6 or lower (32). However, it must be noted that in CRPC samples, the Gleason score is less reliable and could give an erroneously high value.…”
Section: Discussionsupporting
confidence: 81%
“…We could confirm these findings in our experimental models and found higher SRD5A1 levels in metastasized and hormone-refractory tumors. The association between SRD5A1 expression and Gleason score is in line with the observation that patients with a Gleason score of 7 to 10 PC had a smaller decline of intraprostatic DHT concentrations during hormonal therapy compared with patients with a Gleason score of 6 or lower (32). However, it must be noted that in CRPC samples, the Gleason score is less reliable and could give an erroneously high value.…”
Section: Discussionsupporting
confidence: 81%
“…Notably, saturating concentrations of DHT (25 nM) were used in these studies to maximize the significance of the inhibitor effects; however, lower concentrations (1-10 nM) promoted a similar magnitude response (not shown). DHT levels in the prostate have not been accurately determined but are reported to be at least 10 -20 nM (19,20). Pretreatment with the AR antagonist flutamide (Fig.…”
Section: Dht-induced Erk Signaling Occurs Via Matrix Metalloproteinasmentioning
confidence: 99%
“…The enzymatic conversion of DHEA to DHT has been shown to be essential for the activation of AR in LNCaP prostate cancer cells (Evaul et al 2010), while in vitro studies have shown that prostate cancer stromal cells and human LNCaP prostatic cancer cells coordinate activation of AR via synthesis of testosterone and DHT from DHEA (Mizokami et al 2009). In addition, increased expression of genes that code for the enzymes that convert DHEA into testosterone has been observed in CRPC (Stanbrough et al 2006), while cancerous prostatic tissue can synthesize more DHT than does benign prostatic tissue (Nishiyama et al 2007).…”
Section: Mechanisms Of Resistance To Castrationmentioning
confidence: 99%